CULTIVATION OF THE SEAWEED Ulva spp. WITH EFFLUENT FROM A SHRIMP BIOFLOC REARING SYSTEM: DIFFERENT SPECIES AND STOCKING DENSITY - Mateus Aranha MARTINS; Vitor Fernandes da SILVA; Patricio René TARAPUEZ; Leila HAYASHI; Felipe do Nascimento VIEIRA (Boletim do Instituto de Pesca)
This work evaluated the use of effluent from a marine shrimp biofloc rearing system to cultivate the green seaweed Ulva. First, the growth of two Ulva species, U. ohnoi and U. fasciata, was evaluated. Second, the best-performing species was cultivated under two different stocking densities (2 g L-1 and 4 g L-1) to evaluate both growth and nutrient uptake rates, considering total ammonia nitrogen, nitrate, and orthophosphate. In both cases, environmental variables were monitored, and the cultivation medium, consisting of 25% biofloc water and 75% seawater, was exchanged weekly. U. ohnoi grew significantly better, considering all variables evaluated (p<0.05). The smaller stocking density produced a higher specific growth rate (p<0.05). Yield, however, was unaffected (pâ"°¥0.05). No significant differences in the nutrient uptake rates were observed (pâ"°¥0.05). Overall, this work highlights the importance of species selection for seaweed destined for aquaculture. Additionally, it also optimizes the cultivation of seaweeds, specifically U. ohnoi, using effluent from biofloc systems.